Product lifecycle management and the industry of the future : 14th IFIP WG 5.1 International Conference, PLM 2017, Seville, Spain, July 10-12, 2017, Revised selected papers /: 14th IFIP WG 5.1 International Conference, PLM 2017, Seville, Spain, July 10-12, 2017, Revised selected papers. (2017) - Unknown
No abstract available